Advanced materials science & technology in China : a roadmap to 2050 - Lu, Ke; Chen, Lidong; He, Tianbai; Yan, Qing (Beijing : Science Press, 2010)
Materials form the milestones and the physical basis of civilization. Th ere are many kinds of materials. With the development of society, material science and engineering has an urgent research and development mission due to the requirements of increasing materials variety and quality, meeting the diff erent demands, effi cient use of resources, minimizing the environment pollution, etc. Human civilization is labeled by materials: Old Stone Age, New Stone Age, Bronze Age, Iron Age, and Silicon Age(or Electronic Age), which indicates the great impact of materials and related techniques on the development of human society. Nowadays, materials technology is the physical base and forerunner of the transportation, energy & power, resources & environment, electronic information, agriculture and construction, aviation, national defense and military, and many important national projects. There are three mainstays in modern society: materials, energy and information. The need of social economic development on materials is wide and urgent. Demand of new materials is increasing due to the development of national core industry and high-tech. industry. Development of structural materials for energy equipments, energy storage and conversion materials is required to face the challenge of energy problem. Improvement of environment and realization of the harmonious development of human being and nature makes new demands on environmental friendly materials and environment control materials. New materials and production technology are demanded by the exhausted resources, and also the recycling of the materials is very important. Healthcare requires biomedical materials, which include medical apparatus, medical implant materials, drug control release materials and new materials for early diagnosis. Variety and high performance of the information materials are also desired. Higher and rigorous demands are to be satisfi ed in many key projects in the field of aeronautic...
Keywords: CIENCIA DE LOS MATERIALES -- CHINA; MATERIALES -- INVESTIGACIONES -- CHINA; CIENCIA DE LOS MATERIALES -- INNOVACIONES TECNOLOGICAS -- CHINA; CIENCIA Y TECNOLOGIA -- PREDICCIONES -- CHINA